Haemodynamics during Percutaneous Nephrolithotomy in Spinal Anaesthesia with Two Doses of Hyperbaric Bupivacaine (0.75%) - Muhammad Ali, Muhammad Shafiq, Aleena Hassan, Muhammad Ali, Muhammad Shafiq, Aleena Hassan (Journal of Rawalpindi Medical College, 2017)
To compare variation in haemodynamics during percutaneous nephrolithotomy in spinal anaesthesia with two doses of hyperbaric bupivacaine (0.75%). Methods: In this randomized comparative study 60 patients, undergoing percutaneous nephrolithotomy, were included. It was done to compare the variation in haemodynamic parameters after spinal anaesthesia using two different doses of local anaesthetic before and after keeping patients in prone position. Patients were divided into two groups: Group A(n=30) (22.5 mg hyperbaric Bupivacaine 0.75%) and Group B (n=30)(30 mg hyperbaric Bupivacaine 0.75%). Spinal block was performed in sitting position. Hemodynamic measurements were carried out at different time points while patients were in supine and prone position. Results: Decrease in heart rate was significant in Group B than in Group A after 10 minutes of spinal block while in supine position (p<0.001) and the drop in heart rate was significant statistically in Group B when patients were turned to prone position (p<0.001).Systolic and diastolic blood pressures decreased in Group B at 5 and 10 minutes in supine position which further decreased following prone positioning and the decrease was highly significant statistically(p=<0.001). Conclusion: 22.5 mg of injection hyperbaric Bupivacaine is haemodynamically safer as compared to 30 mg of the same drug during spinal anaesthesia in percutaneous nephrolithotomy.